1981
DOI: 10.1002/path.1711350307
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic lesions in shock and their significance

Abstract: The pancreas was examined histologically in 146 cases of patients dying of shock. The finding of morphological evidence of disseminated intravascular coagulation (DIC) in the pancreas supports the opinion that the pancreas in highly sensitive to disturbances of blood perfusion. The presence of DIC combined with a variety of pathological lesions in the exocrine ad endocrine pancreas was sufficiently characteristic to justify use of the term " shock pancreatitis". The relative scarcity of data hitherto available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Ischemic injury to the pancreas has been demonstrated both experimentally and clinically [11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30]. After intra-arterial injection of occluding microspheres into the pancreatic circulation, the severity of the resultant AP varies with the size of the particles [25, 26].…”
Section: Ischemia/reperfusion Injury Of the Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic injury to the pancreas has been demonstrated both experimentally and clinically [11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30]. After intra-arterial injection of occluding microspheres into the pancreatic circulation, the severity of the resultant AP varies with the size of the particles [25, 26].…”
Section: Ischemia/reperfusion Injury Of the Pancreasmentioning
confidence: 99%
“…AP has been observed in several clinical situations involving pancreatic ischemia: selective embolization of the primary vessels supplying the pancreas [41], hypoperfusion of the pancreas during cardiac surgery [11, 17, 18, 21, 22, 23, 28], and visceral hypoperfusion due to hemorrhagic shock [24]. Similarly, pancreas transplantation may lead to AP manifesting early during the posttransplantation period; the etiopathogenesis is presumably multifactorial but nevertheless related to matters of ischemic injury secondary to the low-flow state prior to explanation, obligate harvest ischemia, and reperfusion injury upon revascularization [13, 33].…”
Section: Ischemia/reperfusion Injury Of the Pancreasmentioning
confidence: 99%
“…[24] We found that during 12 hours after admission, serum amylase concentrations were elevated, whereas serum lipase concentrations were below the upper reference limit, suggesting that hyperamylasemia is of non-pancreatic origin. [1] Hegewald et al [25] and Gmaz-Nikulin et al [23] reported the appearance of pancreatic changes during shock, detected only by electron microscopy and histology; in our study, we used imaging techniques, such as ultrasonography and computed tomography, in evaluating the changes of the pancreatic gland, and the pancreatic changes were not clinically relevant. Interestingly, hyperamylasemia was also observed anecdotally in the course of severe sepsis [4] or septic shock.…”
Section: Discussionmentioning
confidence: 91%
“…[10][11][12] Since Panum [13] presented the first report, other researchers have reported that the pancreas is highly sensitive to ischemia. [14][15][16][17][18] In humans, acute pancreatitis may develop after embolic closure of the vessels supplying the pancreas, [19] after hypoperfusion of the pancreas during cardiac surgery [20,21] and surgery for thoraco-abdominal aneurysms, [22] after splanchnic hypoperfusion, [23] or after pancreatic transplantation. [24] We found that during 12 hours after admission, serum amylase concentrations were elevated, whereas serum lipase concentrations were below the upper reference limit, suggesting that hyperamylasemia is of non-pancreatic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis is one aftermath for which there is no treatment. The complication develops in 9 % of patients with haemorrhagic shock and 27 % of patients undergoing cardiac surgery with extracorporeal bypass [115], and to date this problem is unresolved in terms of aetiology and treatment [116]. Experimental studies show that acute pancreatitis is another problem that must be solved at the level of the microcirculation [117].…”
Section: Surgery Reperfusion and Microcirculationmentioning
confidence: 99%